Impact of Training and Development on the Performance of Employees - A Comparative Study on Select Banks in Sultanate Of Oman (International Journal of Scientific Research and Management (IJSRM), 2018)
This paper studies the impact of Training and Development practices on the employee performance in the select Omani Public and Private sector banking organizations. The aim of the paper is to analyze the impact of training and development practices on employee performance. The study adopts descriptive research design and it imbibes both primary and secondary data. Convenience sampling method is applied for collecting the data through administering a structured questionnaire. The sample size for the study is 300. Statistical tools like Pearson Correlation Analysis, Regression Analysis and ANOVA were applied to test the proposed alternate hypothesis. The study concludes that Training and Development Practices have a positive influence on employee performance in the Omani Banking Industry